Islamic Expressive Writing for Psychological Healing - Kurniawan, Redite; Kholis, Nur; Suryani, Suryani (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2025)
Expressive writing, a therapeutic technique shown to alleviate emotional distress, has not been widely adopted in Islamic education despite its proven benefits. This study aims to integrate expressive writing with Islamic principles to support anxiety relief among adolescents in educational settings. Specifically, it compares the outcomes of this intervention in state schools versus Islamic schools, examines gender differences, and assesses the impact of participants’ personalities and social support on the effectiveness of the intervention. The study employed a pretest-posttest control experimental design involving 124 adolescents aged 13 to 15 years from a state school and an Islamic junior high school. Participants were selected based on self-reported anxiety symptoms measured by the Generalized Anxiety Disorder 7 (GAD-7) questionnaire, which has demonstrated strong psychometric properties, with a Cronbach’s alpha of 0.89, indicating high reliability and construct validity supported by correlations with other established anxiety measures. The intervention included expressive writing exercises integrated with Islamic teachings, and anxiety levels were measured pre and post-intervention. The results show that in the state school, the intervention significantly reduced anxiety levels, with an average decrease of 2 points in anxiety scores (p = 0.04). In the Islamic school, the intervention resulted in an average increase of 2.4 points in scores. Integrating expressive writing with Islamic principles can effectively address anxiety among students, creating a more supportive and holistic educational environment. The culturally and spiritually relevant framework enhances the therapeutic impact, indicating significant potential for this approach in both state and Islamic schools.